The Use of The Adventure by Angels & Airwaves as Authentic Material in EFL Vocabulary and Critical Thinking Instruction - Afif Zuhdy Idham; Nurul Hasbi; Arfah Hamzah (Jurnal Pedagogi dan Inovasi Pendidikan, 2026)
This study investigates the integration of alternative rock poetics as authentic instructional material to enhance advanced vocabulary acquisition and higher-order thinking skills (HOTS) among tertiary EFL students. Utilizing a qualitative case study design, this research examined an intact cohort of fourth-semester pre-service English teachers (N = 28) at Universitas Muhammadiyah Barru during the 2025/2026 academic year. The pedagogical intervention was framed around Angels & Airwaves’ metaphor-dense track